2019
DOI: 10.26477/jbcd.v31i3.2693
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy of silver, zinc oxide, and titanium dioxide nanoparticles incorporated in orthodontic bonding agent

Abstract: Background: One of the most important complications of fixed orthodontic treatment is formation of white spots, which are initial carious lesions. Addition of antimicrobial agents into orthodontic adhesive material might be wise solution for prevention of white spots formation. The aim of this study was to evaluate the antibacterial properties of orthodontic adhesive primer against S. Mutans after adding the three different types of nanoparticles (Ag, ZnO, or TiO2). Materials and methods: Discs were prepared u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
2
5
3
Order By: Relevance
“…Nevertheless, these small reductions may also be clinically relevant. The results of some previous studies [33][34][35] contradict our results. Kasraei et al 33 concluded that ZnO had a more significant antimicrobial effect than Ag against S. mutans, but there was no difference between the two nanoparticles' antimicrobial effect against L. acidophilus.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, these small reductions may also be clinically relevant. The results of some previous studies [33][34][35] contradict our results. Kasraei et al 33 concluded that ZnO had a more significant antimicrobial effect than Ag against S. mutans, but there was no difference between the two nanoparticles' antimicrobial effect against L. acidophilus.…”
Section: Discussioncontrasting
confidence: 99%
“…Hailan and Al-Khatieeb 34 demonstrated a reduction in the number of S. mutans colonies around primer discs containing nano-ZnO and nano-Ag, which is consistent with our results. However, in their study, the antimicrobial effect of nano-ZnO against S. mutans was significantly higher than that of nano-Ag, which is inconsistent with the results of our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a comparison of antibacterial activities against S. mutans in three groups of Transbond XT acrylate composites modified with Ag NPs, ZnO NPs, and TiO 2 NPs, the viable bacterial count decreased in all cases. Nevertheless, the antibacterial activity was higher for the TiO 2 NP-containing group than for the Ag NPs and ZnO NP-containing groups, which is due to smaller size of TiO 2 NPs (25 nm) compared with Ag NPs (80 nm) and ZnO NPs (50 nm) [ 87 ].…”
Section: Orthodonticsmentioning
confidence: 99%
“…163,164 Addition of antimicrobial agents to orthodontic material can minimize enamel demineralization. 165 Antimicrobial NPs like ZnO NPs are used mostly in orthodontic applications, including nano-adhesives, composites and GICs. 161 Table 7 summarizes studies examining the use of ZnO NPs in orthodontic applications.…”
Section: Orthodonticsmentioning
confidence: 99%